2013
DOI: 10.7314/apjcp.2013.14.8.4519
|View full text |Cite
|
Sign up to set email alerts
|

Arab Women's Breast Cancer Screening Practices: A Literature Review

Abstract: Materials and MethodsElectronic databases were queried for full text, English language, peer reviewed literature published between 2000 and 2011. These were: Medline (OVID), PubMed, Cochrane Database of Systematic Reviews, CINAHL Plus, Google Scholar, and Index Medicus for WHO Eastern Mediterranean. The Asian Pac J Cancer Prev was searched separately. Keywords that were used singularly and in combination were: Arab, Middle East, Gulf, women, breast cancer, screening, culture, mammography, beliefs, knowledge, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 69 publications
6
65
0
Order By: Relevance
“…This finding of more advanced tumor presentation of BC in BA patients concurs with two previous reports on Palestinian patients residing in the Jerusalem area, and in Arab patients residing in northern Israel (Zidan et al, 2012). A late stage at presentation and locally-advanced BC has typically been reported in studies from Arab countries (Ortashi, 2013), and has been ascribed in these studies to failure to seek medical attention for early but palpable BC (Donnelly et al, 2013). Cultural reluctance to participate in screening mammography programs in the Arab population has been mentioned as a major impediment for early diagnosis of BC in these countries (Bener et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…This finding of more advanced tumor presentation of BC in BA patients concurs with two previous reports on Palestinian patients residing in the Jerusalem area, and in Arab patients residing in northern Israel (Zidan et al, 2012). A late stage at presentation and locally-advanced BC has typically been reported in studies from Arab countries (Ortashi, 2013), and has been ascribed in these studies to failure to seek medical attention for early but palpable BC (Donnelly et al, 2013). Cultural reluctance to participate in screening mammography programs in the Arab population has been mentioned as a major impediment for early diagnosis of BC in these countries (Bener et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Compliance with mammography practices among Saudi women is low compared to European or other Western countries [21,38]. This is because the Arab regional context is different, and regional sociodemographic, cultural, religious and traditional belief systems have to be accounted for, in order to improve breast cancer screening practices [39,40]. This study revealed quantitative measurements in this regard, and recommends health promotion in poorer and less-educated women to increase screening efficacy.…”
Section: Discussionmentioning
confidence: 84%
“…Promotional information should address the importance of early detection in the absence of symptoms, as well as concerns about privacy and fear of diagnosis. Educational materials and messages should clearly explain how early detection of breast cancer can increase women's treatment options and survival rates in the language and manner that is most suitable to the target culture (Donnelly 2006;Donnelly et al, 2013).…”
Section: Discussionmentioning
confidence: 99%